Portable light therapy in the treatment of unipolar non-seasonal major depressive disorder: study protocol for the LUMIDEP randomised controlled trial. Issue 7 (9th July 2021) - Cosker, Eve; Moulard, Marie; Schmitt, Samuel; Angioi-Duprez, Karine; Baumann, Cédric; Laprévote, Vincent; Schwan, Raymund; Schwitzer, Thomas
Abstract : Introduction: Major depressive disorder (MDD) affects more than 264 million people worldwide and is associated with an impaired quality of life as well as a higher risk of mortality. Current routine treatments demonstrate limited effectiveness. Light therapy (LT) on its own or in combination with antidepressant treatments could be an effective treatment, but the use of conventional LT devices use is restrictive. Portable LT devices allow patients to continue with their day-to-day activities and therefore encourage better treatment compliance. They have not been evaluated in MDD. Methods and analysis: The study is a single-centre, double-blind, randomised controlled trial assessing the efficacy of LT delivered via a portable device in addition to usual care (medical care and drug treatment) for inpatients and outpatients with unipolar non-seasonal MDD. Over the course of 8 weeks, patients use the device daily for 30 min at medium intensity as soon as possible after waking up and preferably between 07:00 and 09:00. All patients continue their usual care with their referring physician. N=50 patients with MDD are included. The primary outcome measure is depressive symptom severity assessed using the Montgomery-Åsberg Depression Rating Scale between baseline and the eighth week. Secondary outcome measures are sleep quality assessed using the Pittsburgh Sleep Quality Index and Epworth Sleepiness Scale and anxiety level assessed on the Hamilton Anxiety Rating Scale, between baseline and week 8. Further parameters relating to cognitive function are measured at baseline and after the intervention. An ancillary study aims to evaluate the impact of MDD on the retina and to follow its progression. Main limitations include risk of discontinuation or non-adherence and bias in patient selection. Ethics and dissemination: The study protocol was approved by Ile de France X's Ethics Committee (protocol number 34–2018). Findings will be published in peer-reviewed journals. Trial registration number: NCT03685942 .